Ultra low-power macro-blocks for biomedical applications - Chew, Eng Sue. (2009)
An area-power efficient full-adder is designed in the form of a soft macro and serving as a basic module for the multiplier-less Finite Impulse Response (FIR) filter architecture implementation.